Early Detection of Severe Acute Kidney Injury by Urinary Neutrophil Gelatinase Associated Lipocalin in Critically Ill Children (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Acute Kidney Injury (AKI) is independently associated with worsened morbidity and increased mortality in critically ill children in the Pediatric Intensive Care Unit (PICU). Till date Serum Creatinine (S.Cr) is the gold standard for AKI detection. Urinary Neutrophil Gelatinase-Associated Lipocalin (uNGAL) is revealed as a promising novel biomarker for the early detection of kidney damage. The study is aimed to evaluate the ability of uNGAL for early detection of severe AKI in critically ill children. Materials and methods: This prospective observational study included 90 pediatric ICU (PICU) patients aged 1 month to 12 years from December 2020 to November 2021.Urine was collected for uNGAL on admission (Day 0). Blood samples were collected on Day 0 (D0), Day 3 (D3) and Day 7 (D7) for serum creatinine (S.Cr). AKI was defined and staged according to Kidney Disease Improving Global Outcomes 2012 criteria. Results: Among 90 children, 26 (28.9%) develop severe AKI on D3. The median uNGAL level was 182.9 ng/ml in children with severe AKI compared to 44.3 ng/ml in those without severe AKI. The AUC for the D0 uNGALto predict D3 severe AKI was 0.945 (CI 0.867–1.0). The best cutoff point for uNGAL was 102.70 ng/ml, with a sensitivity of 96.15% and specificity of 98.44% for D3 severe AKI. D0uNGAL had no significant correlation with D0S. Crbut had a significant positive correlation with D3 and D7 S.Cr. Conclusion: Urinary NGAL is an useful early AKI marker to detect the development of severe AKI in critically ill children of PICU.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 29-33